2011
DOI: 10.1088/0031-8949/84/02/025004
|View full text |Cite
|
Sign up to set email alerts
|

Scattering and bound state solutions of the asymmetric Hulthén potential

Abstract: One-dimensional time-independent Schrödinger equation is solved for the asymmetric Hulthén potential. Reflection and transmission coefficients and bound state solutions are obtained in terms of the hypergeometric functions. It is observed that the unitary condition is satisfied in nonrelativistic region.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…[9]. After these pioneering studies, the transmission resonance and supercriticality for the relativistic/non-relativistic particles in an external potentials have been extensively discussed [3,11,12,13,14,15,16,17,18]. In one of these studies [13], the authors showed that the transmission coefficient obtained for the Klein-Gordon particle displays a behavior similar to that of the one obtained for the Dirac particle [8].…”
Section: Introductionmentioning
confidence: 86%
“…[9]. After these pioneering studies, the transmission resonance and supercriticality for the relativistic/non-relativistic particles in an external potentials have been extensively discussed [3,11,12,13,14,15,16,17,18]. In one of these studies [13], the authors showed that the transmission coefficient obtained for the Klein-Gordon particle displays a behavior similar to that of the one obtained for the Dirac particle [8].…”
Section: Introductionmentioning
confidence: 86%
“…It has many applications in atomic physics and condensed-matter physics [14][15][16][17][18][19][20][21][22][23][24]. The Hellmann potential, with 0 V positive, was suggested originally by Hellmann [15,25] and henceforth called the Hellmann potential if 0 V is positive or negative. The Hellmann potential was used as a model for alkali hydride molecules [17].…”
Section: The Hellmann Potentialmentioning
confidence: 99%
“…Analytic solutions have been obtained for the the square well [2,3], Woods-Saxon potential [4], cusp potential [5], and Hulthén potential [6] as well as asymmetric barriers [7,8], multiple barriers [9], and a class of short-range potentials [10]. The successful isolation of graphene [11] has led to renewed interest in the transmission-reflection problem for the one-dimensional Dirac equation.…”
Section: Introductionmentioning
confidence: 99%